Die Corona-Pandemie II Leben lernen mit dem Virus - Schaupp, Walter; Ruckenbauer, Hans-Walter; Platzer, Johann; Kröll, Wolfgang (Bioethik in Wissenschaft und Gesellschaft, 2021)
The ongoing COVID-19 pandemic has confronted us with constantly new challenges. We need to browse new inventories of scientific knowledge to reflect on previous experiences and thus facilitate societal learning. In line with the first volume on the COVID-19 pandemic in this series, contributions from different disciplines and fields of practice create an awareness of the complexity of this crisis and help us to understand the diversity of challenges it poses. The first part focuses on philosophical, sociological and psychological problem diagnoses, the second on reactive strategies in the fields of medicine, nursing care, the economy and law. After taking a look at religious contexts and fields of practice, leading experts from the healthcare sector share their experiences of the COVID-19 pandemic. With contributions by Mahmoud Abdallah, Désirée Amschl-Strablegg, Cornelia Baptist-Kröpfl, Herbert Beiglböck, Ulrike Berdnik, Alois Birklbauer, Anneliese Derkits, Reinhold Esterbauer, Franziska Grossschädl, Katharina Heimerl, Andreas Heller, Marie-Christin Hinteregger, Hartmann Jörg Hohensinner, Elisabeth Horvath, Isabella Jonveaux, Anna-Christina Kainradl, Ulla Kriebernegg, Wolfgang Kröll, Ulrike Kylianek, Martin M. Lintner, Saskia Löser, Christa Lohrmann, Sandra Müller, Gerold Muhri, Manfred Novak, Sabine Petritsch, Eva Peyker, Michaela Pfadenhauer, Barbara Pichler, Johann Platzer, Lisa Pongratz, Maria Puntigam, Elisabeth Reitinger, Hans-Walter Ruckenbauer, Hellmut Samonigg, Walter Schaupp, Georg Tafner, Christa Tax, Wolfgang Toller and Jürgen Wallner.